Preharvest and Postharvest Application of Garlic and Rosemary Essential Oils for Controlling Anthracnose and Quality Assessment of Strawberry Fruit During Cold Storage - Hosseini, Somaieh; Amini, Jahanshir; Saba, Mahmoud Koushesh; Karimi, Kaivan; Pertot, Ilaria (Frontiers in Microbiology, 2020)
This study assessed the feasibility of using essential oils (EOs) against Colletotrichum nymphaeae inciting strawberry anthracnose. Two EOs, extracted from Allium sativum (garlic) and Rosmarinus officinalis (rosemary) were selected because their fungicide efficacy was already well characterized under lab and greenhouse conditions. We characterized both EOs in terms of efficacy and impact on qualitative traits and sensory quality of strawberry fruit. The GC-MS analysis confirmed the allyl trisulfide (29.08%) and (α)-pinene (15.779%) as the main components of A. sativum and R. officinalis EOs, respectively. Both A. sativum and R. officinalis EOs significantly inhibited the mycelial growth and conidial germination of C. nymphaeae in contact and vapor assays compared with untreated control. However, EC50 assay indicated A. sativum EO was more effective than R. officinalis EO against the pathogen. Malformations of the vegetative structures of the pathogen exposed to both EOs were revealed as shriveled, collapsed and swelling mycelia in the cultures. Both EOs confirmed their efficacy under in vivo and greenhouse conditions, in fact they significantly reduced the development of fruit decay and anthracnose disease incidence and severity, compared with untreated controls. Both EOs preserved sensory attributes and quality parameters of strawberry fruit including firmness, total soluble solids, ascorbic acid, antioxidant activity and anthocyanin, but may leave unwanted smells. These findings suggest that two EOs, can potentially represent an alternative to synthetic chemical fungicides against C. nymphaeae preserving fruit quality factors, although their cost and the impact on the fruit odor, must be carefully taken into consideration before developing a commercial product.